Mudrā Pandita MGPSSR Dalam Ritual Hindu Bali (Kajian Teologi, Magis, Estetis) - I Nyoman Nengah Sukanda Arimbawa (Kamaya: Jurnal Ilmu Agama, 2018)
Mudra Pandita In Balinese Hindu Rituals, it is very interesting that attention is sought more deeply. Every time you see Pandita (the general name for the Rev. Hidu Bali) adore, recite the chanting of the mantra of puja with the accompaniment of sounds on some spells of spells being chanted while dancing the two crystals (doing mudrā). Very beautiful and raises high sacredness. The beauty and sacredness according to Hindu service in carrying out his religion which is always based on Satyam, Sivam, Sundaram (truth, holiness, beauty / balance). In each mudrā movement performed by displaying a pose is a symbol that symbolizes the power of God with its various manifestations (Ista Dewata) and with a specific purpose (worship / pleasing and asking for repentance). Therefore, of course this is a Satyam unit (theological truth), he also carries out Sivam (purity) by the process of self-sacralization first, to go to Sundaram (beauty / balance). Why do you have to do the Mudra movement? Is not enough spell puja? People want to offer the best to God. They want their offerings to be truly accepted by God. If words or puja-mantra are not enough, they add body movements and expressions to articulate the meaning of the words. It is very important to understand about the forms, functions, meanings and aspects contained in mudrand Pandita. For this reason a study was conducted on Pandita groups from the social-cultural-religious organization Maha Gotra Pasek Sanak Sapta Rsi (MGPSSR).